Seismic Reflection Images of Possible Mantle-Fluid Conduits and Basal Erosion in the 2011 Tohoku Earthquake Rupture Area - Park, Jin-Oh; Tsuru, Tetsuro; Fujie, Gou; Jamali Hondori, Ehsan; Kagoshima, Takanori; Takahata, Naoto; Zhao, Dapeng; Sano, Yuji (Frontiers in Earth Science, 2021)
Multi-channel seismic reflection and sub-bottom profiling data reveal landward-dipping normal faults as potential conduits for mantle-derived fluids in the coseismic slip area of the 2011 Tohoku earthquake (Mw9.0). Normal faults below the helium isotope anomaly sites appear to develop through the forearc crust (i.e., the seafloor sedimentary section and Cretaceous basement), potentially extending down to the mantle wedge, despite their intermittently continuous reflections. The faults are characterized by high-amplitude, reverse-polarity reflections within the Cretaceous basement. Moreover, deep extension of the faults connecting to a low-velocity region spreading from the Cretaceous basement into the mantle wedge across the forearc Moho suggests that the faults are overpressured by local filling with mantle-derived fluids. The locations of the normal faults are roughly consistent with aftershocks of the 2011 Tohoku earthquake, which show normal-faulting focal mechanisms. The 2011 Tohoku mainshock and subsequent aftershocks can lead the pre-existing normal faults to be reactive and more permeable so that locally trapped mantle fluids can migrate up to the seafloor through fault fracture zones. Elevated fluid pressures can decrease the effective normal stress for the fault plane, facilitating easier slip along landward-dipping normal faults, thereby enhancing their tsunamigenic potential. The landward-dipping normal faults developing from the seafloor down into the Cretaceous basement are predominant in the middle slope region of the forearc. A possible shear zone with high-amplitude, reverse-polarity reflections above the plate interface, which is almost localized to the middle slope region, suggests more intense basal erosion of the overlying plate in that region.